Biceps tendon subluxation associated with isolated greater tuberosity fracture and bony Bankart lesion without a Hill-Sachs lesion: A case report and review of the literature - Maalouly, Joseph (Trauma Case Rep, 2020)
Combined injuries of the glenohumeral joint that involve biceps tendon subluxation associated with isolated greater tuberosity fracture and bony Bankart lesion are extremely rare. As per our knowledge, this is the first case report that includes such combined injuries that were treated arthroscopically. We present the case of a 48-year-old male patient who sustained shoulder trauma after being thrown against the rocks by a wave, was found to have biceps tendon subluxation associated with isolated greater tuberosity fracture and bony Bankart lesion. The operative management resulted in complete restoration of the range of motion of the shoulder, and uneventful healing of the fracture. The patient recovered normal activity including his surfing.